Structural Equation Modeling of Socioeconomic Influences on Maternal Health Utilization and Outcomes in Nigeria - Hadiza Sami Musa (INTERNATIONAL JOURNAL OF APPLIED SCIENCE AND MATHEMATICAL THEORY, 2026)
This study examines the influence of socioeconomic status (SES) on maternal health outcomes in Nigeria using data from the 2018 Nigeria Demographic and Health Survey (NDHS), conducted by the National Population Commission in collaboration with ICF International. A Structural Equation Modeling (SEM) framework was employed to assess both direct and indirect relationships among socioeconomic factors, maternal health utilization, and health outcomes. The measurement model was validated using Confirmatory Factor Analysis (CFA), with all observed variables demonstrating strong factor loadings (≥ 0.72), confirming construct validity. Convergent validity and reliability were further supported by satisfactory Composite Reliability (CR ≥ 0.85) and Cronbach’s Alpha values (≥ 0.83). The structural model results reveal that socioeconomic status has a significant positive effect on maternal health utilization (β = 0.41, p = 0.002) and maternal health outcomes (β = 0.32, p = 0.009). Furthermore, decomposition of effects shows that SES exerts an additional indirect effect on maternal health outcomes through utilization (β = 0.15), yielding a substantial total effect of β = 0.47. This confirms a partial mediation mechanism, where improved socioeconomic conditions enhance healthcare utilization, which in turn leads to better maternal health outcomes. The model explains 42% (R² = 0.42) of the variance in maternal health utilization and 47% (R² = 0.47) of the variance in maternal health outcomes, indicating moderate to strong explanatory power. Effect size analysis shows that SES has a medium effect (f² = 0.18) on maternal health utilization. Additionally, multicollinearity diagnostics indicate no significant concerns (VIF < 5), ensuring the robustness of the estimates. The findings underscore the critical role of socioeconomic empowerment— particularly income, education, and financial autonomy—in improving maternal healthcare utilization and outcomes in Nigeria. The study recommends targeted policy interventions aimed at reducing socioeconomic inequalities, expanding access to health insurance, and improving women's education to enhance maternal health outcomes.